Harmonic Analysis and Compensation Strategy for Grid-connected Inverter with LCL Filter - Xiaowei Dong; Yize Sun; Yujie Chen; Jie Yang (Institute of Advanced Engineering and Science, 2014)
In this paper, the harmonic components of grid-connected current are systemically and quantitatively analyzed, including the high-frequency harmonics caused by the modulation, and the low-frequency harmonics injected by the inherent non-linear characteristics and dead-time effects of switching tubes along with the DC voltage secondary pulsation and the grid disturbance. Furthermore, a combined control scheme of repetitive control and state feedback is brought forward, in which the feedforward decoupling for DC voltage and the feedforward compensation for grid voltage are added. The proposed control strategy can eliminate resonance peak of LCL filter, suppress and compensate the low-frequency harmonics, so that quick response and tracking without static error of the system can be realized. Finally, the rationality of the presented harmonic analysis and the validity of the presented combined control scheme are verified on the 3kW inverter experiment system.DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3578